Traditional Game-Based Learning for Mathematics in Elementary School: A Systematic Literature Review - Wardani, Mesa; Izzatul Himmah, Wulan (Universitas Islam Negeri Raden Intan Lampung, 2026)
Traditional game-based learning has attracted growing attention in elementary mathematics education because it links formal mathematical concepts with cultural experience, concrete activity, and social interaction. However, empirical findings remain scattered across different game types, cultural resources, methodological designs, and mathematical domains. This study aims to synthesize research on traditional game-based mathematics learning in elementary schools and to clarify its pedagogical position within ethnomathematics-based instruction. A Systematic Literature Review design guided by the PRISMA 2020 framework was employed. Articles were identified through Google Scholar and screened using predetermined inclusion and exclusion criteria. From 221 initial records, 15 empirical studies published between 2021 and 2025 were included in the synthesis. Data were analyzed through descriptive mapping and thematic synthesis, focusing on publication trends, research methods, subjects, data collection techniques, traditional game or cultural resources, mathematical content, and reported learning contributions. The findings show that research on this topic developed steadily, with the highest number of studies appearing in 2025. Qualitative research dominated the corpus, followed by design research, while quantitative evidence remained limited. Elementary school students were the most frequent research subjects, and observation was the most common data collection technique. Traditional game and ethnomathematical resources supported arithmetic, geometry, measurement, spatial reasoning, numeracy, motivation, cooperation, participation, and cultural pride. This review contributes by reframing traditional game as cultural artifacts, learning media, instructional design contexts, and representational systems, while emphasizing the need for empirical designs, validated instruments, teacher involvement, and systematic classroom implementation.